evaluate the expression Let x = - 1/3 and z = 5/6

(1 + x) (1 + z) =

Thank you for the opportunity to help you with your question!

(1 + x) (1 + z) = (1 - 1/3) (1 + 5/6)

(1 + x) (1 + z) = ((3 - 1)/3) ((6 + 5)/6)

(1 + x) (1 + z) = (2/3) (11/6)

(1 + x) (1 + z) = 22/18 = 11/9

I just want to verify that I am doing this correctly and that my answer is correct or not correct. can you please help me with this problem by checking it over?

Add:

1/7 + 4/7 = 5/7. am I correct with 5/7?

yes dear your answer is correct..........

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up